Named Entity Disambiguation Anaphora Resolution and Question Answering in Speech - Chithira, C H (International Journal of Computer Sciences and Engineering, 2018)
Speech Recognition, Named Entity Disambiguation(NED), Anaphora Resolution and Question Answering(QA) are some of the major areas of research in Natural Language Processing(NLP). Speech recognition systems will convert the human voice into corresponding text. Named Entity Disambiguation will identify the entity types in the given text. Anaphora Resolution is the process of finding antecedents of an anaphor and it has become a challenging task in the Computational Linguistics and Natural Language Processing(NLP). Question answering will develop systems that automatically answers the questions in natural language. Question answering system and Named Entity Disambiguation are the important fields intended to enhance the performance of the Information Retrieval System. This work mainly focused on integrating the above three tasks in a single system. Moreover this system will perform these tasks by receiving human speech as input and then converting it into the corresponding text. After the text conversion, Entity Disambiguation is performed on it. Real time speech input are given as the input. Anaphora resolution is also integrated with the disambiguation phase. The Question Answering System completely depends on the efficiency of entity disambiguation. The Answers are retrieved by searching based on these disambiguated entities. Anaphora Resolution will provide greater support for those entities that are not correctly identified in the disambiguation phase. Also the problem that anaphors that couldn't find proper antecedents can easily find the correct ones since their entity type is correctly identified. The Question Answering System will perform better if the entities are correctly identified and disambiguated.